Genetic and clinical characteristics of catecholaminergic polymorphic ventricular tachycardia in a Taiwanese nationwide cohort - Grace Chia-Yen Hsu; Mei-Hwan Wu; Jing-Yuan Chuang; Shuenn-Nan Chiu; Ming-Tai Lin; Ling-Ping Lai; Shih-Fan Sherri Yeh; Sheng-Fu Liu; Ting-Tse Lin; Fu-Tien Chiang; Jyh-Ming Jimmy Juang (Journal of the Formosan Medical Association, 2025)
Background: Catecholaminergic polymorphic ventricular tachycardia (CPVT) is a rare and lethal arrhythmia. Ryanodine receptor 2 (RYR2) mutation accounts for ∼60% of CPVT patients which is inherited in an autosomal dominant pattern. Objective: This study aimed to identify CPVT-related mutations and clinical characteristics among Taiwanese CPVT patients and compare to other cohorts worldwide. Methods: Clinical and genetic data were obtained from the Sudden Arrhythmia Death Syndrome Registry in Taiwan (SADS-TW). Forty clinically diagnosed Taiwanese CPVT patients were included. Results: This is the first nationwide CPVT cohort in Taiwan. Among the 29 Taiwanese patients with CPVT-related gene mutations, 55% had RYR2 mutations, a rate similar to other ethnicities. Three out of 12 RYR2 variants were unreported. Exercise-induced symptoms including syncope and cardiac arrest were more frequent in East Asian cohorts (Taiwanese 79%, Japanese 91%), compared to Caucasian cohorts (59%) (p = 0.002). Conclusion: The discovery of diverse RYR2 mutations in the Taiwanese CVPT population demonstrates the importance of genetic testing in different ethnicities.